Comparative Optoelectronic Study between Copolymers of Peripherally Alkylated Dithienosilole and Dithienogermole - Fei,Z; Kim,Y; Smith,J; Buchaca,Domingo E; Stingelin,N; McLachlan,MA; Song,K; Anthopolous,TD; Heeney,M (Macromolecules, 2012)
Here we report a simple methodology for the synthesis of dithienosilole and dithienogermole monomers in which the necessary solubilizing long chain alkyl groups are incorporated into the peripheral 3,5-positions of the fused ring. We report four novel monomers in which methyl or butyl groups are attached to the bridging Si and Ge atom. Copolymers with bithiophene were synthesized by a Stille polymerization in high molecular weight. We report the optical, electrical, electrochemical and morphological properties of the resulting polymers. We find that the nature of the bridging heteroatom (Si or Ge) has only a minor influence on these properties, whereas the nature of the alkyl chain attached to the bridging atom is found to have a much larger effect.